Current pretreatment/cell disruption and extraction methods used to improve intracellular lipid recovery from oleaginous yeasts - Zainuddin, Muhammad Fakhri; Chong, Kar Fai; Ariff, Arbakariya; Rios-Solis, Leonardo; Halim, Murni (Multidisciplinary Digital Publishing Institute, 2021)
The production of lipids from oleaginous yeasts involves several stages starting from cultivation and lipid accumulation, biomass harvesting and finally lipids extraction. However, the complex and relatively resistant cell wall of yeasts limits the full recovery of intracellular lipids and usually solvent extraction is not sufficient to effectively extract the lipid bodies. A pretreatment or cell disruption method is hence a prerequisite prior to solvent extraction. In general, there are no recovery methods that are equally efficient for different species of oleaginous yeasts. Each method adopts different mechanisms to disrupt cells and extract the lipids, thus a systematic evaluation is essential before choosing a particular method. In this review, mechanical (bead mill, ultrasonication, homogenization and microwave) and nonmechanical (enzyme, acid, base digestions and osmotic shock) methods that are currently used for the disruption or permeabilization of oleaginous yeasts are discussed based on their principle, application and feasibility, including their effects on the lipid yield. The attempts of using conventional and “green” solvents to selectively extract lipids are compared. Other emerging methods such as automated pressurized liquid extraction, supercritical fluid extraction and simultaneous in situ lipid recovery using capturing agents are also reviewed to facilitate the choice of more effective lipid recovery methods.